Edukasi Pembuatan Biskuit Salut Coklat Bagi Anak-Anak - Savitri, Dyah Ayu; Novijanto, Noer; Nadzirah, Rufiani; Suud, Hasbi Mubarak (Universitas Mataram, 2024)
Chocolate is a cocoa derivative product that is liked by various age groups, from children, teenagers, adults to the elderly because it has a distinctive taste and is considered capable of improving a person's mood due to the content of alkaloids and proteins such as tryptophan. Coated biscuits are biscuit products that are dipped or coated with chocolate, giving the product a richer taste. This educational program was carried out by introducing how to make chocolate-coated biscuits for children in Jember. The objectives of implementing this service are: (1) developing children's creativity, (2) training in making chocolate-coated biscuits and (3) developing children to like the activity of processing plantation products. This program will provide broader knowledge and skills so that children have higher self-confidence. Education on making chocolate-coated biscuits for children provides an interesting experience in the field of food product processing and can stimulate children's motoric development.